SaNum dan SaLis: Strategi Mempersiapkan Asesmen Kompetensi Minimum di Sekolah Dasar - Muhammad Fakhri Saifudin; Markhamah; Fitri Puji Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Minimum Competency Assessment is currently one of the goals in achieving quality education. Minimum Competency Assessment is often associated with literacy and numeracy. It is a fundamental assessment of students' competencies to develop their inner abilities and participate in community social activities. This study aims to analyze the preparation of the Minimum Competency Assessment in primary schools through Numeracy Breakfast and Literacy Breakfast activities. The methods used in this research are observation, interview, and documentation methods with the subjects of elementary school students, teachers, and principals. The instrument used was an observation sheet. After the data is collected, it is then analyzed using the interactive analysis method with stages according to Miles and Huberman, namely reducing data, presenting data and drawing conclusions guided by the results of this study indicate that guidance and training activities to face the Minimum Competency Assessment, namely with the Numeracy Breakfast and Literacy Breakfast strategies starting from group formation, looking for reading books in the library, reading and numeracy activities, and writing activities. So, it can be concluded that the level of literacy and numeracy skills of students is still very low; in overcoming this problem, the researcher saw that the school implemented a literacy movement called Sarapan Numerik (SaNum) and Sarapan Literasi (SaLis). The Numeracy Breakfast and Literacy Breakfast activities are innovations in preparing for the Minimum Competency Assessment in Primary Schools.